Maslow and Rogers’ Humanistic Theory: A Conceptual Analysis and Its Implications for Islamic Education - Marlina, Cut Nyak; Ak, Warul Walidin; Mahmud, Salami (Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia., 2025)
This article aims to analyze the humanistic learning theories proposed by Abraham Maslow and Carl Rogers, examining their implications for Islamic education. The study employed a library research method, reviewing literature sources such as books, journal articles, and scientific works relevant to humanistic theory and Islamic education. The steps for conducting this research are as follows: 1) Preparing tools and equipment in the form of ideas and research topics; 2) Compiling relevant information on the topic; 3) Maintaining discipline in terms of time and clarifying the focus of the research; 4) Classifying reading materials; 5) Reading and compiling research notes; 6) Enriching reading materials; 7) Writing the research. The results show that Maslow's hierarchy of needs theory emphasizes the importance of fulfilling students' basic needs, from physiological and safety needs to social and esteem needs, and ultimately, self-actualization. This fulfillment greatly influences motivation and learning success. In the context of Islamic education, understanding these needs is important for educators to design effective strategies and methods and create a conducive learning environment. Meanwhile, Carl Rogers's humanistic theory emphasizes meaningful learning and freedom in learning. It also emphasizes the role of educators as facilitators who provide empathy, unconditional acceptance, and sincerity. Rogers' theory has clear implications for Islamic education, as evidenced by efforts to help students achieve self-realization according to their unique potential, not only cognitively, but also affectively and psychomotoriy. Thus, integrating Maslow and Rogers' humanistic theories into Islamic education can encourage students to become faithful individuals with noble character who can practice Islamic values in their daily lives. Abstrak Artikel ini bertujuan untuk menganalisis secara konseptual teori belajar humanistik yang dikemukakan oleh Abraham Maslow dan Carl Rogers serta mengkaji implikasinya dalam pembelajaran Pendidikan Agama Islam (PAI). Penelitian ini menggunakan metode library research dengan menelaah berbagai sumber literatur berupa buku, artikel jurnal, dan karya ilmiah yang relevan dengan teori humanistik dan pendidikan Islam. Adapun langkah-langkah dalam melaksanakan penelitian ini adalah: 1) menyiapkan alat perlengkapan berupa ide serta topik penelitian; 2) menyusun informasi yang relevan dengan topik; 3) disiplin waktu dan pertegas fokus penelitian; 4) klasifikasikan bahan bacaan; 5) membaca dan menyusun catatan penelitian; 6) melakukan pengayaan bahan bacaan; 7) menuliskan penelitian. Hasil kajian menunjukkan bahwa teori hierarki kebutuhan Maslow menegaskan bahwa pemenuhan kebutuhan dasar peserta didik, mulai dari kebutuhan fisiologis, rasa aman, sosial, penghargaan, hingga aktualisasi diri, sangat berpengaruh terhadap motivasi dan keberhasilan belajar. Dalam konteks pembelajaran PAI, pemahaman terhadap kebutuhan tersebut menjadi landasan penting bagi pendidik dalam merancang strategi, metode, dan lingkungan belajar yang kondusif. Sementara itu, teori humanistik Carl Rogers menekankan pentingnya pembelajaran yang bermakna (significant learning), kebebasan belajar, serta peran pendidik sebagai fasilitator yang memberikan empati, penerimaan tanpa syarat, dan ketulusan. Implikasi teori Rogers dalam pembelajaran PAI tampak pada upaya membantu peserta didik mencapai perwujudan diri (self-realization) sesuai dengan potensi dan keunikan masing-masing, tidak hanya pada aspek kognitif, tetapi juga afektif dan psikomotorik. Dengan demikian, integrasi teori humanistik Maslow dan Rogers dalam pembelajaran Pendidikan Agama Islam mampu mendorong terbentuknya peserta didik yang beriman, berakhlak mulia, mandiri, serta mampu mengamalkan nilai-nilai ajaran Islam dalam kehidupan sehari-hari.